2011
DOI: 10.1002/gps.2674
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of restless legs syndrome among psychogeriatric patients

Abstract: RLS is a frequent condition in psychogeriatric patients, especially among those with depression, and is commonly underdiagnosed and undertreated. Clinicians should routinely ask for RLS symptoms when assessing their patients in their regular clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
10
1
1
Order By: Relevance
“…Many studies have indicated that RLS is not associated with the use of antidepressants, and some studies have suggested that antidepressants might exacerbate RLS symptoms. [ 17 18 19 ] In addition, depression did not improve as significantly as the symptoms of RLS in our study. Thus, we believe that rTMS alleviates RLS directly rather than through the treatment of associated symptoms.…”
Section: Discussioncontrasting
confidence: 68%
“…Many studies have indicated that RLS is not associated with the use of antidepressants, and some studies have suggested that antidepressants might exacerbate RLS symptoms. [ 17 18 19 ] In addition, depression did not improve as significantly as the symptoms of RLS in our study. Thus, we believe that rTMS alleviates RLS directly rather than through the treatment of associated symptoms.…”
Section: Discussioncontrasting
confidence: 68%
“…Population-/community-based studies 22,23,[29][30][31][32][33][34][35][36][37][38][39][40] and clinicbased studies 18,25,[41][42][43][44][45] have consistently demonstrated an increased prevalence or risk of depression and/or anxiety in 44 . In the majority of cases, the onset of RLS occurred prior to that of the psychiatric disorder.…”
Section: Depressive and Anxiety Disordersmentioning
confidence: 99%
“…Differential diagnosis may be difficult in cognitively impaired patients with affective disorders, who may have difficulty explaining their array of sensory complaints and distinguishing them from psychiatric complaints. 25 Recognition of RLS is particularly important in patients receiving treatment for mood disorders and anxiety, as some of the medications commonly used to treat insomnia and depression may result in exacerbation of RLS symptoms.…”
Section: Diagnosis Of Rlsmentioning
confidence: 99%
“…24 Among 99 elderly patients attending a Spanish psychiatric clinic, the prevalence of confirmed RLS was 11%. 25 An additional 10% of patients had "possible RLS"; the diagnosis could not be confirmed due to doubts regarding the accuracy and reliability of the information provided by the patient. None of the patients in the study had previously been diagnosed with RLS.…”
mentioning
confidence: 99%